Comparing loops misconceptions in block-based and text-based programming languages at the K-12 level - Mladenović, Monika; Boljat, Ivica; Žanko, Žana (Education and information technologies, 2018)
Novice programmers are facing many difficulties while learning to program. Most studies about misconceptions in programming are conducted at the undergraduate level, yet there is a lack of studies at the elementary school (K-12) level, reasonably because computer science neither programming are regularly still not the part of elementary school curricula’s. Are the misconceptions about loops at elementary school level equal to those at the undergraduate level? Can we “prevent” the misconceptions by using the different pedagogical approach, visual programming language and shifting the programming context toward game programming? In this paper, we tried to answer these questions. We conducted the student misconceptions research on one of the fundamental programming concepts – the loop. The research is conducted in the classroom settings among 207 elementary school students. Students were learning to program in three programming languages: Scratch, Logo and Python. In this paper, we present the results of this research.